Insulation corkboard carbon content and CO2 equivalent - Gil, Luís (2011)
In this work the carbon content of insulation corkboard (ICB), an insulation (thermal, sound and vibration) material based on cork is quantified and based on this the CO2 equivalent is determined, in order to evaluate the capacity of CO2 sequestration of this material in comparison with other competitive materials, namely for building applications (sustainable construction).